Parenting Patterns as A Determinant of Stunting in Toddlers Under Five Years in Indonesia - Elvika Aulia Fitroningtyas (Jurnal KESANS : Kesehatan dan Sains, 2021)
Stunting is identified as one of the unresolved nutritional problems in several countries in the world, including Indonesia. Stunting is identified as impacting the growth and development of children's motor, psychomotor, and mental conditions, and intelligence. One of the efforts to reduce the risk of stunting is to identify and analyze the pattern of parenting provided by mothers to toddlers. Parenting can be defined as parenting behavior for toddlers related to efforts to provide food and fulfill nutritional needs, provide access to health facilities, and care in other aspects based on knowledge, attitudes, and mother's behavior. Aims to analyze parenting as a determinant of stunting in Indonesia through the article review method. The type of the article is article review based on ten main articles that have been selected based on inclusion and exclusion criteria. Parenting has a relationship and contribution as a determinants of stunting in toddlers in Indonesia. Parenting patterns can be broadly classified into three types: parenting patterns according to the provision of food and nutrients, parenting patterns according to health aspects, and parenting patterns according to mother and family background.